The Phonological Ordering Constraint of the Short-Before-Long Preference Tendency in Qassimi Arabic Binomial Phrases: a Quantitative Analysis - Alzaidi, Muhammad Swaileh (International Journal of Language and Literary Studies, 2022)
Research on the phonological constraints on the linear order in binomial phrases has proven that the tendency to place the short conjunct before the long one can be active differently in different languages. The current research addresses the short-before-long preference tendency in binomials in Qassimi Arabic. It shows that Qassimi Arabic binomials manifest the short-before-long preference in three possible forms: (1) the conjunct containing the fewer phonemes (i.e., the shorter item) tends to precede the one containing the more phonemes (i.e., the longer item) within the same binomial phrase, (2) the conjunct containing the fewer syllables (i.e. the shorter item) tends to precede the one containing the more syllables (i.e. the longer item) within the same binomial phrase, and (3) the conjunct containing the shorter vowel (i.e. the shorter item) tends to precede the one containing the longer vowel (i.e. the longer item) within the same binomial phrase. To approve the real existence of these proposed hypotheses in Qassimi Arabic binomials, the study adopts a quantitative analysis which has largely been adopted in relevant studies. The findings of the quantitative analysis of a big number of binomials (336 binomial pairs) indicate the satisfaction rates for the three hypotheses posited in the current study are statistically highly significant. Therefore, the study concludes that there is definite evidence for the factual existence of the short-before-long preference in Qassimi Arabic binomials, a finding which is compatible with similar studies in binomials in English and some other European languages.